Ecological Labelling in North-South Trade - Wilhelm Althammer; Susanne Dröge (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
We investigate in a horizontal product differentiation model with North-South trade the implications of a home bias in consumers' demand for labelled goods. We compare mutual recognition and international harmonisation of ecological labels with respect to firms' profits and welfare. Northern consumers perceive a warm glow from buying green, but have information problems with imported labelled products. Firms differ in labelling costs which could help a Southern firm to compensate for the home bias under mutual recognition. Under harmonisation the home bias disappears. Welfare analysis of harmonised labelling shows that a Southern firm gains from adopting a harmonised label even if there is "eco-imperialism". Given the specific trade structure in our model, harmonisation is a beneficial regime except for the case that labelling costs reach a specific treshold.
Keywords: L13; Q56; F13; F18; 330; Ecological Labels; Product Differentiation; North-South Trade; WTO Rules